Irrigation Strategies with Controlled Water Deficit in Two Production Cycles of Cotton - Wellinghton Alves Guedes; Reginaldo Gomes Nobre; Lauriane Almeida dos Anjos Soares; Geovani Soares de Lima; Hans Raj Gheyi; Pedro Dantas Fernandes; Ana Paula Nunes Ferreira; André Alisson Rodrigues da Silva; Carlos Alberto Vieira de Azevedo; Daniel Valadão Silva; José Francismar de Medeiros (Plants, 2023)
Water scarcity is one of the main abiotic factors that limit agricultural production. In this sense, the identification of genotypes tolerant to water deficit associated with irrigation management strategies is extremely important. In this context, the objective of this study was to evaluate the morphology, production, water consumption, and water use efficiency of colored fiber cotton genotypes submitted to irrigation strategies with a water deficit in the phenological phases. Two experiments were conducted in succession. In the first experiment, a randomized block design was used in a 3 × 7 factorial scheme, corresponding to three colored cotton genotypes (BRS Rubi, BRS Jade, and BRS Safira) in seven irrigation management strategies with 40% of the real evapotranspiration (ETr) varying the phenological stages. In the second experiment, the same design was used in a 3 × 10 factorial arrangement (genotypes × irrigation management strategies). The water deficit in the vegetative phase can be used in the first year of cotton cultivation. Among the genotypes, ‘BRS Jade’ is the most tolerant to water deficit in terms of phytomass accumulation and fiber production.